Identification of Shoreline Shifts and Subsurface Layers Using Google Earth Pro with the Multichannel Analysis of Surface Wave (MASW) Method in the Abrasion-Prone Areas of Central Bengkulu to Seluma - Putri, Adinda Permata; Refrizon, Refrizon; Hadi, Arif Ismul; Sinaga, Yuni Kharisma; Jaya, Shara Ashari Prana (Jurnal Fisika dan Aplikasinya, 2024)
Abstract: Central Bengkulu to Seluma is mostly abraded and slightly accreted. Shoreline changes occur as a result of sediment movement, wave action, ocean currents, and human activities. This study aims to determine, analyze changes in the coastline from North Bengkulu to Seluma using Google Earth Pro and determine the value of rock stratigraphic layers using the Multichannel Analysis of Surface Wave (MASW) method. Field data collection was carried out using the Seismograph PASI 16S-24P seismic tool. The results of mapping and validation of primary data that has been inversed and then processed in surfer software, show that the beach with the largest abrasion value over a span of 16 years is Muara Dua beach in track 3, with a shoreline change of 6.7m / year. Then based on the value of Vs the coastal area of Central Bengkulu to Seluma is divided into 3 class sites, namely class D stiff soil, C very dense soil and soft rock and B medium rock.